Eles não são intocáveis: histórias de quem foi isolado por causa da hanseníase - Pereira, Vinícius Borges [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The book features profiles in which are told histories of people who, because of having leprosy, have had experienced periods of great prejudice. Even in the 80s, there were still cases of compulsory hospitalization of patients. In other words, people were forced to withdraw from society because they had Hansen's disease. The narrative of the personal histories, at the book, is broken by explanations regarding to the disease and by the development of important aspects concerning the historical theme

O livro apresenta perfis, que contam as trajetórias de pessoas que vivenciaram períodos de grande preconceito pelo fato de serem portadoras de “lepra”. Até na década de 80, ainda existiam casos de internação compulsória de pacientes. Ou seja, as pessoas eram obrigadas a se afastar da sociedade pelo fato de sofrerem do Mal de Hansen. A narração das histórias é entrecortada por explicações esclarecedoras referentes à doença e pelo desenvolvimento de aspectos históricos importantes concernentes à temática abordada
Keywords: Doenças - Epidemiologia; Jornalismo cientifico; Hanseniase - Brasil; Hanseniase - Hospitais; Diseases - Epidemiology